(3aJM GdeLjO HcaGjI GdeQjOs - (3YHO GdSdGe Hf EHQGgje GdeGdcj GddbGfis; (3CMeO Hf YHO Gddg GdNQGjQj, CHh GdYHGSs
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ YHO GdSdGe Hf EHQGgje GdeGdci GddbGfi gPG JYdjb dWja Ydi efXheI GdYGQa HGddg JYGdi SjOi CHG GdYHGS CMeO Hf YHO Gddg GdNQGjQi s
(3BNQgG (B:s
(3hbGd LYaQ GdUGOb QVi Gddg Yfg gd LRG ef CMSfJ Edjg ai GdCRd EdG MaX GdEMSGf Ydjg ai GdcHO hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje hCaVd GdUdGI hCTQa GdJSdje Ydi SjOfG eMeO GdeNUhU HeRjO GdJcQje hYdi Bdg hUMHg CLeYjf Edi jhe GdOjf s
(3CJe JCdjag SfI (B1057 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds